-100y+30=17+9x

Simple and best practice solution for -100y+30=17+9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -100y+30=17+9x equation:


Simplifying
-100y + 30 = 17 + 9x

Reorder the terms:
30 + -100y = 17 + 9x

Solving
30 + -100y = 17 + 9x

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-30' to each side of the equation.
30 + -30 + -100y = 17 + -30 + 9x

Combine like terms: 30 + -30 = 0
0 + -100y = 17 + -30 + 9x
-100y = 17 + -30 + 9x

Combine like terms: 17 + -30 = -13
-100y = -13 + 9x

Divide each side by '-100'.
y = 0.13 + -0.09x

Simplifying
y = 0.13 + -0.09x

See similar equations:

| 6x^3+5x^2-21x=0 | | 6a^3-9a^2+15a=0 | | X+6+3x=15-2x | | (4+3i)/(2+i) | | 1/2x+27=-50 | | 5x+2=3(-7x+6)-8(-2-3x) | | 6r^3-31r^2+35r=0 | | 24+3x=3x+7(7-1) | | 4x^2+34x+42=0 | | -16t^2+60t-40=0 | | -35x^2-4x+15=0 | | 8(2.5x-0.75)-0.25(1-x)=0.5 | | -16t^2+60t=40 | | -15a^2-16a+15=0 | | 8(x+6)-9=40-5x-1+13x | | 8(x+6)-9=40-5x-1+13 | | -2+4(x-4)=13x+2-9x | | -(3z-4)=6z-3(3z+2) | | 0.8x-0.4(9-3x)=-0.2(x-4) | | 31-5(x+1)=x | | sqrt(x-2)=x-3 | | x+4y=-7 | | 4t/-9=-5 | | 5/54-2/24-3/96 | | x^2+4x=286 | | 5-2w/3=10 | | 2=12x^2+2x | | -16t^2+32t+256=0 | | x^2+15x=76 | | (2x-3)(3x+9)= | | 9(t-2)+3t=6(2t+4)-9 | | 2x=12x^2+2x |

Equations solver categories